Custom genotyping for substance addiction susceptibility genes in Jordanians of Arab descent - AL-Eitan Laith N; Jaradat Saied A; Hulse Gary K; Tay Guan K (BMC Research Notes, 2012)
Abstract Background Both environmental and genetic factors contribute to individual susceptibility to initiation of substance use and vulnerability to addiction. Determining genetic risk factors can make an important contribution to understanding the processes leading to addiction. In order to identify gene(s) and mechanisms associated with substance addiction, a custom platform array search for a genetic association in a case/control of homogenous Jordanian Arab population was undertaken. Patients meeting the DSM-VI criteria for substance dependence (n = 220) and entering eight week treatment program at two Jordanian Drug Rehabilitation Centres were genotyped. In addition, 240 healthy controls were also genotyped. The sequenom MassARRAY system (iPLEX GOLD) was used to genotype 49 single nucleotide polymorphisms (SNPs) within 8 genes (DRD1, DRD2, DRD3, DRD4, DRD5, BDNF, SLC6A3 and COMT). Results This study revealed six new associations involving SNPs within DRD2 gene on chromosome 11. These six SNPs within the DRD2 were found to be most strongly associated with substance addiction in the Jordanian Arabic sample. The strongest statistical evidence for these new association signals were from rs1799732 in the C/−C promoter and rs1125394 in A/G intron 1 regions of DRD2, with the overall estimate of effects returning an odds ratio of 3.37 (χ2 (2, N = 460) = 21, p-value = 0.000026) and 1.78 (χ2 (2, N = 460) = 8, p-value = 0.001), respectively. It has been suggested that DRD2, dopamine receptor D2, plays an important role in dopamine secretion and the signal pathways of dopaminergic reward and drug addiction. Conclusion This study is the first to show a genetic link to substance addiction in a Jordanian population of Arab descent. These findings may contribute to our understanding of drug addiction mechanisms in Middle Eastern populations and how to manage or dictate therapy for individuals. Comparative analysis with different ethnic groups could assist further improving our understanding of these mechanisms.